Crab contributions as an ecosystem engineer to sediment turnover in the Yellow River Delta - Xie, Tian; Wang, Andong; Li, Shanze; Cui, Baoshan; Bai, Junhong; Shao, Dongdong (Frontiers in Marine Science, 2022)
Burrowing crabs are widely distributed and have large populations in estuarine wetlands. Crab excavation can have potentially significant bioturbation effects on the vertical structure of sediments, and the processes of nutrients deposition and mineralization. However, the effects of crab micro activities on the geochemical cycling processes of the whole estuarine ecosystems are not clear, specifically the contributions of burrowing crabs to sediment and nutrients turnover in coastal ecosystems. Due to the lack of knowledge on crab burrowing behavior and borrow morphology, it is difficult to accurately estimate the excavation and turnover volumes of crabs. Therefore, this study examined the bioturbation activity of the crab Helice tientsinensis in western Pacific estuary ecosystems by analyzing their burrow morphology and local sediment properties. The common burrow shapes of Helice tientsinensis were J- and Y-shaped burrows. Burrow morphological characteristics such as total burrow depth, curve burrow length, burrow volume, and opening diameter significantly differed among tidal zones. Crab carapace size, water depth, soil hardness, and bulk density were the main factors driving burrow morphology. Sediment excavation by crabs was ~50 times greater than the deposition of sediment into crab burrows. The net transported amounts of sediment (31.66–33.18 g·d-1·m-2) and nutrients (total nitrogen: 0.075–0.090 g·d-1·m-2, total carbon: 3.96–4.55 g·d-1·m-2, and organic matter: 0.44–0.77 g·d-1·m-2) were mainly from the belowground sediment to the surface. These results highlighted the important role of crabs in sediment and nutrients cycling within coastal estuary ecosystems.